2016
DOI: 10.1080/2162402x.2015.1137418
|View full text |Cite
|
Sign up to set email alerts
|

NKp30 isoforms and NKp30 ligands are predictive biomarkers of response to imatinib mesylate in metastatic GIST patients

Abstract: Despite effective targeted therapy acting on KIT and PDGFRA tyrosine kinases, gastrointestinal stromal tumors (GIST) escape treatment by acquiring mutations conveying resistance to imatinib mesylate (IM). Following the identification of NKp30-based immunosurveillance of GIST and the off-target effects of IM on NK cell functions, we investigated the predictive value of NKp30 isoforms and NKp30 soluble ligands in blood for the clinical response to IM. The relative expression and the proportions of NKp30 isoforms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 40 publications
1
56
0
Order By: Relevance
“…The presence of high levels of NKp30C isoform in blood NK cells influences GIST patient's prognosis 11 and markedly impacted both event-free and OS, in two independent cohorts of metastatic GIST. 28 Low DBC values and low expression levels of NKp30A were identified in one-third of patients with dismal prognosis across molecular subtypes. This low DBC value in PBMC was associated with a pro-inflammatory and immunosuppressive tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of high levels of NKp30C isoform in blood NK cells influences GIST patient's prognosis 11 and markedly impacted both event-free and OS, in two independent cohorts of metastatic GIST. 28 Low DBC values and low expression levels of NKp30A were identified in one-third of patients with dismal prognosis across molecular subtypes. This low DBC value in PBMC was associated with a pro-inflammatory and immunosuppressive tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…11 In particular, the NK infiltrate predicts progression-free survival in GIST, and patients classified as immunological responders on the basis of NK-interferon levels showed a better survival while treated with imatinib. 12 Tumor-infiltrating lymphocytes (TIL) are the second most enriched immune cell population in GIST samples. 9,11,13,14 Balachandran et al demonstrated that CD8 + T cells contribute to antitumor effects of imatinib.…”
Section: Introductionmentioning
confidence: 99%
“…In these cases, the release of such ligands in the extracellular environment may represent an effective mechanism to dampen NK cell function, not only in physiologic immune interactions but also in tumor-driven escape strategies. 37-40 In this context, soluble ligands, endowed with suppressive capability, have been described for NKG2D and DNAM-1 activating receptors (sMICA, sULBPs, and sPVR) and for NKp30 (sB7H6 and sBAT3/BAG6). 32,33,35,41-50 On the other hand, extracellular ligands for NKp46 and NKp44 have been recently identified and demonstrated to have a positive effect on the NK cell function.…”
Section: Introductionmentioning
confidence: 99%